Household energy consumption in the United States - Giuseppe Ruggeri (Zenodo, 2022)
This paper provides estimates of household energy consumption in the United States in 2019 by adding passenger transportation to residential consumption. It also separates household energy consumption into two components: standard and optional and shows that the latter accounts for 29 percent of the total.
Keywords: J10; J20; 330; energy consumption; household energy; United States energy